Accesibilidad en espacios protegidos: las áreas de uso público de la Reserva de la Biosfera de Monfragüe - Leco Berrocal, Felipe; Pérez Díaz, Antonio; Mateos Rodríguez, Beatriz (Geographicalia, 2014)
Protected natural areas are currently in Spain there are more than 50 million visitors, bearing in mind that the right to the environment should be universal to all people, public use areas, such as Reserve World Biosphere Monfragüe should be tailored and standardized forwidespread use at all. People with functional diversity in Spain reached 3.5 million people, it is therefore a growing market segment within the tourism sector annually. This research aims to highlight that a large part of public use areas of protected areas do not allow access to these people,while the main points that should be making adjustments in them.
Keywords: accessibility; public use area; protected natural area; tourism.